The association of middle ear effusion with trigeminal nerve mass lesions in dogs. (9th November 2013) - Wessmann, A.; Hennessey, A.; Goncalves, R.; Benigni, L.; Hammond, G.; Volk, H. A.
Abstract : The trigeminal nerve is involved in the opening of the pharyngeal orifice of the Eustachian tube by operating the tensor veli palatini muscle. The hypothesis was investigated that middle ear effusion occurs in a more severe disease phenotype of canine trigeminal nerve mass lesions compared with dogs without middle ear effusion. Three observers reviewed canine MRIs with an MRI‐diagnosis of trigeminal nerve mass lesion from three institutions. Various parameters describing the musculature innervated by the trigeminal nerve were scored and compared between dogs with and without middle ear effusion. Nineteen dogs met the inclusion criteria. Ipsilateral middle ear effusion was observed in 63 per cent (95% CI 48.4 per cent to 77.6 per cent) of the dogs. The size of the trigeminal nerve mass lesions was positively correlated with the severity of masticatory muscle mass loss (Spearman r=0.5, P=0.03). Dogs with middle ear effusion had a significantly increased generalised masticatory muscle mass loss (P=0.02) or tensor veli palatini muscle loss score (P=0.03) compared with those without. Larger trigeminal nerve mass lesions were associated with a greater degree of masticatory muscle mass loss. Masticatory muscle mass and, importantly, tensor veli palatini muscle mass was more severely affected in dogs with middle ear effusion suggesting an associated Eustachian tube dysfunction.